Performance of generalist hemiparasitic Euphrasia across a phylogenetically diverse host spectrum. Issue 5 (9th October 2021) - Brown, Max R.; Moore, Paloma G. P.; Twyford, Alex D.
Summary: Generalist hemiparasites may attach to many different host species and experience complex parasite–host interactions. How these parasite–host interactions impact on the fitness of hemiparasitic plants remain largely unknown. We used experimentally tractable eyebrights ( Euphrasia, Orobanchaceae) to understand parasite–host species interactions affecting the performance of a generalist hemiparasitic plant. Common garden experiments were carried out measuring Euphrasia performance across 45 diverse hosts and in different parasite–host combinations. We show that variation in hemiparasite performance can be attributed mainly to host species and host phylogenetic relationships ( λ  = 0.82; 0.17–1.00 CI). When variation in performance is considered temporally, annual host species cause earlier flowering, and lead to poorer performance late in the season. While Euphrasia species typically perform similarly on a given host species, some eyebrights show more specialized parasite–host species interactions. Our results show that generalist hemiparasites only benefit from attaching to a limited, but phylogenetically divergent, subset of hosts. The conserved responses of divergent Euphrasia species suggest hemiparasite performance is affected by common host attributes. However, evidence for more complex parasite–host species interactions show that a generalist hemiparasite can potentially respond to individual host selection pressures and may adapt to local host communities.